Individual placement and support an evidence-based approach to supported employment - Drake, Robert E., 1949-; Bond, Gary R.; Becker, Deborah R. (New York ; Oxford : Oxford University Press, 2013)
This comprehensive monograph synthesizes the research on the individual placement and support model of supported employment for people with severe mental illness. It identifies empirical foundations for core principles of the model and reviews the literature on effectiveness, long-term outcomes, and policy implications.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: People with mental disabilities -- Employment -- United States; People with mental disabilities -- Services for -- United States